2003
DOI: 10.1021/ie020999u
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Enhanced Oxidation of Oxalic Acid in Water with Cobalt Catalysts. 2. Heterogeneous Catalytic Ozonation

Abstract: Ozone and a Co 3 O 4 /Al 2 O 3 catalyst have been used to remove oxalic acid from water at acidic pH. The influence of different variables, including the initial oxalic acid and ozone gas concentrations, the catalyst mass, and the temperature, has been investigated under conditions of chemical control. The ozone efficiency was found to reach values of up to 40%, which are higher than those found in homogeneous catalysis (see also the first part of this work, which immediately precedes this paper in this issue)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 11 publications
2
30
0
4
Order By: Relevance
“…However, the application of ozonation is still limited due to its selective reactions with organic pollutants (Beltrán et al 2003). In order to overcome this limitation, a lot of improved ozonation was developed (Guo et al 2015;Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of ozonation is still limited due to its selective reactions with organic pollutants (Beltrán et al 2003). In order to overcome this limitation, a lot of improved ozonation was developed (Guo et al 2015;Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…MnO 2 , Fe 2 O 3 , Co 3 O 4 , and NiO had been found effective in the catalytic ozonation of oxalic acid but the removal rates at normal pHs in a reasonable reaction time were too low and the ozone doses were too high for practical uses. 5,7,11,12 There are still no data on ozone consumption for oxalate degradation which is critical to evaluate the catalysis efficiency. No evidence shows active sites and active oxidant species that are responsible for oxalate degradation, the information ABSTRACT: The cerium supported palladium oxide (PdO/ CeO 2 ) at a low palladium loading was found very effective in catalytic ozonation of oxalate, a probe compound that is difficult to be efficiently degraded in water with hydroxyl radical oxidation and one of the major byproducts in ozonation of organic matter.…”
Section: ' Introductionmentioning
confidence: 99%
“…It was reported that effective catalytic oxalate degradation with several typical metal oxides were achieved only at much lower pHs (e.g., 4.1 and 3.2 for MnO 2 , 2.5 for Fe 2 O 3 and Co 2 O 3 , and 2.4 for NiO) and continuous ozone introduction during the reaction over 30 min. 5,7,11,12 This binary oxide seems to be more efficient for practical catalytic ozonation reaction.…”
mentioning
confidence: 96%
“…Beltrán e colaboradores 49 fizeram um estudo mostrando a eficiência do cobalto em solução, imobilizado sobre Al 2 O 3 . Os resultados apresentados para o metal suportado foram bastante promissores e observou-se uma total mineralização do ácido oxálico.…”
Section: Ozônio Catalítico Homogêneounclassified